Metabolites With Cytotoxic Activities From the Mangrove Endophytic Fungus Fusarium sp. 2ST2 - Chen, Yan; Wang, Guisheng; Yuan, Yilin; Zou, Ge; Yang, Wencong; Tan, Qi; Kang, Wenyi; She, Zhigang (Frontiers in Chemistry, 2022)
Two new 3-decalinoyltetramic acids derivatives with a peroxide bridge fusarisetins E (1) and F (2), one new chromone fusarimone A (5), two new benzofurans fusarifurans A (9) and B (10), three new isocoumarins fusarimarins A-C (11-13), as well as five known analogues 3, 4, 6-8 and 14, were isolated from mangrove endophytic fungus Fusarium sp. 2ST2. Their structures and absolute configurations were established by spectroscopic analysis, DFT-GIAO NMR calculation with DP4+ statistical analysis and ECD calculation. Compounds 1 and 2 showed significant cytotoxicity against human A549 cell lines with IC50 values of 8.7 and 4.3 μM, respectively.